International myeloma working group consensus recommendations on imaging in monoclonal plasma cell disorders - Hillengaß, Jens; Usmani, Saad; Goldschmidt, Hartmut (The lancet. Oncology, 2019)
Summary - Recent advances in the treatment of multiple myeloma have increased the need for accurate diagnosis of the disease. The detection of bone and bone marrow lesions is crucial in the investigation of multiple myeloma and often dictates the decision to start treatment. Furthermore, detection of minimal residual disease is important for prognosis determination and treatment planning, and it has underscored an unmet need for sensitive imaging methods that accurately assess patient response to multiple myeloma treatment. Low-dose whole-body CT has increased sensitivity compared with conventional skeletal survey in the detection of bone disease, which can reveal information leading to changes in therapy and disease management that could prevent or delay the onset of clinically significant morbidity and mortality as a result of skeletal-related events. Given the multiple options available for the detection of bone and bone marrow lesions, ranging from conventional skeletal survey to whole-body CT, PET/CT, and MRI, the International Myeloma Working Group decided to establish guidelines on optimal use of imaging methods at different disease stages. These recommendations on imaging within and outside of clinical trials will help standardise imaging for monoclonal plasma cell disorders worldwide to allow the comparison of results and the unification of treatment approaches for multiple myeloma.
Gesehen am 25.06.2019